UNLEASHING LEARNING POTENTIALS AMONG PASSIVE STUDENTS - Mohd Nur Fitri Mohd Salim; Asmahanim Haji Mohamad Yusuf; Irma Ahmad; Mohamad Safwat Ashahri Mohd Salim (Journal of Islamic, Social, Economics and Development, 2020)
There is a significant relationship between students’ passiveness in the classroomwith the level of their motivation in a learning environment. This heavily influences the outcomeof a particular learning goal, since motivation has a significant impact to students’ level ofeffort to learn. This paper discussed on the importance for educators to explore the needs ofpassive students in order to ensure that these students will not be left behind in achieving thelearning goals in the classroom. This includes the need to evaluate the students learningpreferences, understanding the reasons for them to be passive and the roles of teachers infacilitating these students to achieve their full learning potentials. This includes the efforts thatare needed from the teacher to experiment with various teaching and classroom managementskills, since it is found that teachers who are able to cater to the needs of passive students wereable to produce positive outcomes and nurture better learning habits among passive students